(untitled) (Nigerian Journal of Physiological Sciences, 2020)
One of the substances used in force ripening fruits is commercial grade calcium carbide (CaC2) which contains impurities such as arsine and this has been associated with low birth weight and fetal loss. There is thus a need to further investigate additional risks on offspring. This study was thus designed to evaluate the possible effects of maternal consumption of banana pulp force ripened with CaC2 on the offspring. Sixteen pregnant rats were randomly divided into two test groups and controls of four rats each. Two test groups were fed with pelletized feed mixed with banana pulp ripened by commercial grade CaC2 at concentrations of 50g/5kg and 100g/5kg while the controls had a group fed with pelletized feed mixed with normal ripened banana and another had only pelletized feed. This feeding pattern was done morning and evening ad libitum throughout the gestation period of twenty-one days after which only pelletized feed and water was administered. At delivery, all male offspring were separated and each dam was allowed eight female pups to nurse. Upon weaning after twenty-one days, the mothers were removed leaving eight female offspring in each group. Development of their reproductive system was monitored and recorded using parameters such as vaginal opening day (VOD) and reproductive hormonal assay at the sixth week. A fertility test was also carried out by introducing viable male rats for mating at sixth week postpartum. Trace amount of arsenic was found in the banana pulp of 100g/5kg CaC2 group (0.35ppb). CaC2 exposure was related to delayed onset in puberty, decreased serum FSH and a decreased fertility rate in the 100g/5kg CaC2 group (p<0.05). Consumption of contaminated CaC2 ripened fruits exposes humans to arsenic acid which has harmful effects on reproductive development of offspring.